ChemInform Abstract: A Mild and Regioselective Route to Functionalized Quinazolines. Issue 9 (February 2016) - Maiden, Tracy M. M.; Swanson, Stephen; Procopiou, Panayiotis A.; Harrity, Joseph P. A.
Abstract: Starting with aryloxazolines (I) derived from benzoic acids a new route for the synthesis of quinazolines is developed.